Second language writing : (Cambridge Univ. Press, 1996)
This book covers the major issues writing teachers face in setting agendas for teaching writing to nonnative speakers. The book further provides a historical view of the evolution in approaches to the teaching of second language writing and a coherent view of current approaches and issues.